2015
DOI: 10.1080/01930826.2015.1105051
|View full text |Cite
|
Sign up to set email alerts
|

Competency-Based Talent Management: Three Perspectives in an Academic Library

Abstract: This article describes how the University of Utah's J. Willard Marriott Library implemented a competency-based, talent management system across the organization management system across the organization process to address organizational, departmental, and individual needs. Success of the implementation was mixed. Designing human resources systems around core competencies made organizational values and goals concrete but proved unsustainable in the long-term. Using core competencies to shape departmental goals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…During the systematic literature review on TM in HE we found that several authors (Mohan et al, 2015;Peet et al, 2010;Rutledge et al, 2016) were concerned about competency management and/or certain competencies of talents, but they didn't define talents by their competencies.…”
Section: Talent Potentialsmentioning
confidence: 99%
“…During the systematic literature review on TM in HE we found that several authors (Mohan et al, 2015;Peet et al, 2010;Rutledge et al, 2016) were concerned about competency management and/or certain competencies of talents, but they didn't define talents by their competencies.…”
Section: Talent Potentialsmentioning
confidence: 99%
“…Focus on the specialised competencies of human resources in banking and finance will align the recruitment system with organisational goals; using specialised competencies and talents will be followed by organisational plans and competitive advantage (Egeberg et al, 2017). Prospection in the recruitment system makes it possible to provide human resources with minimal cost and to provide the necessary cost to meet all goals of human resources management (Murray et al, 2017: Rutledge et al, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, organisations must be able to identify competent personnel, provide them with the training and experience they need, and recruit and consequently retain the human resources required (Rutledge et al, 2016). Recruiting competent human resources has recently become one of the biggest challenges for organisations; organisations, both private and public, regard the development and retention of their talented employees as vital.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a competitive advantage in organizations, many researchers argue that strategic talent management (STM) is a mechanism to help organizations achieve objectives.This is why many organizations and managers are seeking to develop a talent management strategy (Naulleau 2018). The talent mind-set has helped organizations in recruiting the best talents (Rutledge et al 2016; Sharma and Bhatnagar 2009).However; talent competencies proved very difficult to incorporate across the institution without significant administrative support and commitment to longterm sustainability (Rutledge et al 2016).Human capital management can be used to promote the majority of employees' talents through attraction, development, deployment, and retention practices (M. Christina Meyers, van Woerkom, and Dries 2013).In fact, talent management includes a complete set of processes in order to identify, employ and manage individuals to implement business strategy successfully (Tafti, Mahmoudsalehi, and Amiri 2017).…”
Section: Strategic Talent Management In Organisationmentioning
confidence: 99%